Energy conversion efficiency in sugarcane under two row spacings in northeast of Brazil - Ricardo A. Ferreira; José L. de Souza; Gustavo B. Lyra; João F. Escobedo; Marshall V. C. Santos (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The study aimed to evaluate growth and physical environment of cultivation to determine the efficiency in which the sugarcane, cultivated in two row spacing configurations, converts solar radiation into biomass in Alagoas state - Northeastern of Brazil. For this purpose, the sugarcane variety RB98710 was cultivated, in plot with a single spacing and other with combined spacing. Biometric and solarimetric measurements were performed to evaluate plant growth and net radiation inside the canopy. The extinction coefficient (k), radiation use efficiency (RUE), specific heat of combustion, energy stored in dry matter (DM) and energy conversion efficiency (ECE) were determined for both row spacings. Plants of cultivated with single spacing had k value equal to 0.48 (± 0.03) and value of k with combined spacing was 0.51 (± 0.02). The RUE of sugarcane plants were 2.73 (± 0.09) and 2.78 (± 0.25) g MJ-1 of intercepted photonsynthetically active radiation (R2 = 0.96 and 0.83) in single and combined spacing, respectively. The average specific heat of combustion of the different sugarcane parts was equal to 16,300 J g-1 of DM, but the DM value of stalks was equal to 15,600 J g-1. Thus, the ECE values were 4.4 and 4.5% respectively for crops with single and combined row spacings.